Reconstruction of the palaeoenvironment and anthropogenic activity from the Upper Pleistocene/Holocene anthracological records of the NE Iberian Peninsula (Barcelona, Spain) - Allué, Ethel (2018)
This paper presents the results of anthracological analyses conducted to further the palaeoenvironmental reconstruction of NE Iberia and to provide better insights into the impact of human activity on the landscape. This study is based on the analysis of charred plant remains from five archaeological sites located ~20 km to the southwest of the city of Barcelona. The site chronology spans from the Upper Pleistocene to the mid-Holocene. The MIS 5-stage is represented by the Cova del Rinoceront (ca. 74e175 ka), which yielded scarce anthracological remains, composed primarily of angiosperms. MIS 3 and the HS4 stadial are represented by the Cova del Coll Verdaguer (ca. 33.4e55 ka) and the Terrasses de la Riera dels Canyars (39.6 ka cal BP) respectively, both pointing to the recurrent presence of Pinus sylvestris type. The Holocene record is represented by the Cova Bonica (ca. 7200e4600 cal BP), presenting a predominance of Quercus, Pinus and a considerable variability of shrubs and small tree types. Finally, Cal Maurici (ca. 6100e3700 cal BP) constitutes a natural deposit in shallow marshes, and presents charcoals washed down the river. The sequence presented is completed and compared with other sequences located in NE Iberia. The assemblages allow us to evaluate the evolution and transformation of the forested landscapes originated by the climate variations that occurred during the Upper Pleistocene and Holocene and to assess changes in the woody vegetation resulting from cultural or natural transformations. These outcomes are discussed in terms of a comparison of natural vs. anthropogenic anthracological records and the data are contextualized and examined in the broader context of the other assemblages recovered in the NE Iberian Peninsula.